Epithelial-mesenchymal transition in asthma: its role and underlying regulatory mechanisms - Zhang, Bingxi; Feng, Xinru; Tian, Lincha; Xiao, Bo; Hou, Lixia; Mo, Biwen; Yao, Dong (Frontiers in Immunology, 2025)
Bronchial asthma (asthma) is a respiratory disease characterized by chronic inflammation, airway hyperresponsiveness, and airway remodeling. Numerous studies have delved into asthma’s pathogenesis, among which epithelial mesenchymal transition (EMT) is considered one of the important mechanisms in the pathogenesis of asthma. EMT refers to the transformation of epithelial cells, which lose their original features and acquire a migratory and invasive stromal phenotype. EMT contributes to normal physiological functions like growth, development, and wound healing. However, EMT is also involved in the occurrence and development of many diseases. Currently, the precise regulatory mechanism linking EMT and asthma remain obscure. Increasing evidence suggests that airway EMT contributes to asthma pathogenesis via dysregulation of associated control mechanisms. This review explores EMT’s significance in asthma and the regulatory networks associated with EMT in this context.